Elevated levels of macromolecular damage are correlated with increased nitric oxide synthase expression in erythrocytes isolated from twin neonates - Dugmonits Krisztina Nikoletta (BRITISH JOURNAL OF HAEMATOLOGY, 2016)
Pregnancy is a state associated with an enhanced metabolism and demand for O2 , which may lead to the overproduction of reactive oxygen species (ROS) and hence to oxidative stress. An elevated ROS level may result in delayed development and a low birth weight. The aim of this study was to reveal the consequences of multiple pregnancies on the redox status of neonatal human red blood cells (RBCs) and evaluate the role of endothelial nitric oxide synthase (NOS3) - expressing RBCs in the generation of oxidative stress. The study presents evidence of higher levels of production of hydrogen peroxide, peroxynitrite and nitrate content in the RBCs of twin neonates, clearly reflected by an elevated level of protein and lipid damages. This phenotype appears to be a consequence of multiple pregnancies, regardless of the level of maturity or the birth weight of the twins. Besides the higher level of ROS, there was a general decrease in the expression of genes coding for antioxidants. The first data are presented on NOS3-expressing neonatal human RBCs. The number of RBCs producing NOS3 was more than twice as high in twin neonates compared to singletons, with no correlation to maturity.